"Randomised controlled trial of scalp cooling for the prevention of chemotherapy induced alopecia". (February 2020) - Bajpai, J.; Kagwade, S.; Chandrasekharan, A.; Dandekar, S.; Kanan, S.; Kembhavi, Y.; Ghosh, J.; Banavali, S.D.; Gupta, S.
Abstract: Background: Randomized controlled trials (RCT) of scalp cooling (SC) to prevent chemotherapy induced alopecia (CIA) did not evaluate its effect on hair regrowth (HR) and was conducted in a predominantly taxane (T) treated population. We conducted an RCT of SC in a setting of anthracycline (A) and taxane chemotherapy (CT) and assessed its effect on CIA and HR. Methods: Non-metastatic breast cancer women undergoing (neo) adjuvant CT were randomized to receive SC using the Paxman scalp cooling system during every cycle of CT, or no SC. The primary end point (PEP) was successful hair preservation (HP) assessed clinically and by review of photographs after CT. HR was assessed at 6 and 12 weeks. Results: 51 patients were randomized to SC (34) or control arm (17) in a 2:1 ratio. Twenty-five (49%) patients received A followed by T and the two arms were balanced with respect to this factor. HP rate was significantly higher in SC arm compared to control arm (56.3% vs 0%, P = 0.000004). HR was higher in SC arm compared to control at 6 weeks (89% vs 12%; P < 0.001) and 12 weeks (100% vs 59%, P = 0.0003). Loss of hair at PEP evaluation, which was a quality of life measure, was significantly lower in SC versus control arm (45% vs 82%, P = 0.016). There were no grade 3–4 cold related adverse effects. Conclusions: Women with breast cancer receiving A or T chemotherapy receiving SC were significantly more likely to have less than 50% hair loss after CT, superior hair regrowth and improvement in patient reported outcomes, with acceptable tolerance. It merits wider usage.